Gira...gira...girassol: movimentos de construção de diretrizes curriculares para a educação do campo no sistema municipal de ensino de Cachoeira do Sul/RS - Oliveira, Elke Quiliao de (2021)
This Professional Master's Dissertation is bound to the Programa de Pós-Graduação em Políticas Públicas e Gestão Educacional /UFSM, entitled: "Gira...Gira...Girassol: Movements for the construction of curricular guidelines for Rural Schools in the Sistema Municipal de Educação of Cachoeira do Sul/RS", presents the following issue: What are the specificities of a public policy of Rural Schools in the Sistema Municipal de Educação of Cachoeira do Sul/RS and possible elements that contribute to the elaboration of Curricular Guidelines for the countryside schools of this municipality? Its general objective is to understand the specificities of Rural Schools in the Sistema Municipal de Educação de Cachoeira do Sul/RS, in order to elaborate Municipal Curricular Guidelines for the consolidation of a local public policy that prioritizes the knowledge of rural subjects, and specific objectives: Analyze the public educational policies that guide the rural schools at federal, state, and municipal levels;To analyze the public policies that regulate and guide the countryside schools in the city of Cachoeira do Sul/RS; To build a diagnostic view of the countryside schools in the city of Cachoeira do Sul/RS; To develop, in a shared way, a draft of the Curricular Guidelines for the countryside education in the Sistema Municipal de Educação in the city of Cachoeira do Sul/RS, which prioritizes the knowledge, demands, and needs of the countryside subjects. The methodology used for the research was a qualitative approach, and the data construction tools were: bibliographic research, document analysis, application of questionnaires to the 15 managers of rural schools in the municipality, and semi-structured interviews with the municipal secretary of education and the pedagogical director of the Secretaria Municipal de Educação - SMEd. From the data collected, we used the content analysis technique proposed by Bardin (2006), considering the following categories: Public Policies for Rural Schools; Management of the Rural School; and Sistema Municipal de Educação. As a product of this study, from the results obtained in the research, a draft proposal of the Curricular Guidelines for the Sistema Municipal de Educação of Cachoeira do Sul/RS was built, as well as an agenda for presentation and discussion with the COMDECampo, the Secretaria Municipal de Educação, the City Hall, the Conselho Municipal de Educação, and the Conselho Municipal de Educação e Câmara de Vereadores for the consolidation of a policy for rural schools in the Sistema Municipal de Educação de Cachoeira do Sul.